Organizational Participation and Academic Performance: The Moderating Role of Time Management - Idam Wahyudi; Anggun Sulistyowati; Yoshua Ronaldo Primartono (Universitas Islam Negeri (UIN) Salatiga, 2025)
The present study aims to examine the effect of student organizational involvement on academic achievement and to assess the moderating role of time management in this relationship. Data were collected using a quantitative approach through a closed-ended questionnaire based on a five-point Likert scale, developed from indicators previously tested for validity and reliability. The findings indicate that student engagement in organizational activities significantly contributes to improved academic performance by fostering essential competencies, including communication, leadership, collaboration, and responsibility. Furthermore, this study provides novel empirical evidence by demonstrating that time management functions as a critical moderating mechanism in this relationship, whereby ineffective time management weakens the positive impact of organizational involvement on academic achievement. These results suggest that organizational participation supports academic success only when accompanied by strong time-management skills. However, the use of purposive sampling from a single private university may limit the generalizability of the findings, and caution is therefore required when extending the conclusions to broader higher education contexts. Future research may employ mixed-methods designs to complement quantitative findings with qualitative insights and explore additional moderating or mediating variables, such as self-discipline, burnout, or self-regulated learning, to offer a more comprehensive understanding of the factors shaping students’ academic achievement.